Adverse family experiences during childhood and adolescent obesity. Issue 3 (8th February 2016) - Heerman, William J.; Krishnaswami, Shanthi; Barkin, Shari L.; McPheeters, Melissa
Abstract : Objective: To evaluate the association between adverse family experiences (AFEs) during childhood and adolescent obesity and to determine populations at highest risk for AFEs. Methods: A cross‐sectional analysis was performed of the 2011‐2012 National Survey of Children's Health, including children aged 10‐17 years. Weighted estimates of 31, 258, 575 children were based on interviews with 42, 239 caregivers. Caregiver reports of nine psychosocial risk factors measured AFEs during childhood. Adolescent overweight and obesity were derived by caregiver‐reported child height and weight. Results: Nearly one‐third (30.5%) of children had experienced ≥2 AFEs, with geographic variation by state. The prevalence of obesity among children experiencing ≥2 AFEs was 20.4%, when compared with 12.5% among children with 0 AFEs. Adjusted survey regression models were controlled for child, parent, household, and neighborhood characteristics. Children with ≥2 AFEs in childhood were more likely to have obesity (AOR = 1.8; 95% CI = 1.47‐2.17; P  < 0.001) than those with no AFEs, with Non‐Hispanic, White children most affected. Conclusions: Adolescents in this national sample who were exposed to greater numbers of AFEs in childhood also had higher rates of overweight and obesity. Geographic variation and differential associations based on race/ethnicity identified children at greatest risk.